1982
DOI: 10.1002/1097-0142(19820915)50:6<1204::aid-cncr2820500631>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Selection of patients with malignant ascites for a peritoneovenous shunt

Abstract: Twenty‐two patients with intractable malignant ascites who received a peritoneovenous shunt were studied. We found that the peritoneovenous shunt functioned longer in patients whose ascitic fluid was negative for malignant cells. The median shunt survival in alive patients in the negative cytologic group was 140 days compared to 26 days in the positive cytologic group (P = 0.01). The overall survival of these patients was poor, with a median of 32 days. Median survival of patients with positive cytologic resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…11,25,26 Reductions in platelet count and fibrinogen level and a corresponding increase in the prothrombin time have been reported in other recent series as limited contributors to morbidity and mortality rates. 8,10,11,23,24,27 In the current series, these changes after PVS placement did not demonstrate a statistical association with poorer survival. Unlike others, 26 fibrin split product (FSP) measurement was not performed uniformly in our patients (3 patients had preprocedure FSP values measured; 11 patients had positive postoperative FSP values).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…11,25,26 Reductions in platelet count and fibrinogen level and a corresponding increase in the prothrombin time have been reported in other recent series as limited contributors to morbidity and mortality rates. 8,10,11,23,24,27 In the current series, these changes after PVS placement did not demonstrate a statistical association with poorer survival. Unlike others, 26 fibrin split product (FSP) measurement was not performed uniformly in our patients (3 patients had preprocedure FSP values measured; 11 patients had positive postoperative FSP values).…”
Section: Discussionmentioning
confidence: 47%
“…This is in contrast to an earlier report from Memorial Hospital (New York, NY) suggesting that patients with positive cytology should not be considered as candidates for peritoneovenous shunting. 8 A number of investigators have demonstrated that those patients with peritoneal carcinomatosis, a predictor of poor outcome, are more likely to have positive cytology. 12,15,17 Some have suggested that patients with malignant ascites and negative cytology may have advanced liver disease, which is, in The 51% complication rate seen in the current series is high but is comparable to others.…”
Section: Discussionmentioning
confidence: 99%
“…Routine laboratory methods were used for blood coagulation, hematologic studies, and biochemical monitoring. Quality of life was measured by the re- Ovary (11)(12)(13)(14)(15)(16) All Gastrointestinal (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) ..........…”
Section: Methodsmentioning
confidence: 99%
“…Other new therapeutic approaches to be pointed out include immunotherapy with interferon, tumor necrosis factor, Corynebacterium parvum, and Streptococcal preparation OK-432 [117].…”
Section: Therapeutic Approach For the Patients With Ascitesmentioning
confidence: 99%